Distributed acoustic sensor based on improved minimum control recursive average algorithm - Wang, Yu; Guo, Maosen; Liu, Xin; Bai, Qing; Wang, Dong; Zhang, Mingjiang; Jin, Baoquan (Optical fiber technology, 2019)
•Application of improved minimum control recursive average algorithm in optical fiber sensor.•Sensing system consists of a double Sagnac interference structure to pick up acoustic signals.•Location ability verification of metal tapping signals with several types of noise.•Positioning error after the IMCRA algorithm is reduced. An optical fiber acoustic sensor based on the combination of generalized cross-correlation and improved minimum control recursive average algorithms is proposed. The sensing system consists of a double Sagnac interference structure that picks up acoustic signals along the sensing fiber. The improved minimum control recursive average algorithm is used to preprocess the acquired signal to improve the signal-to-noise ratio, then the time-delay information is obtained through the correlation operation on the processed signal, and the acoustic source is located through the time delay information. Experiments show that under the condition of high signal-to-noise ratio of the acquired signal, the accuracy of acoustic source localization can be improved.